KONSEP BELAJAR MENURUT ISLAM DAN PARA TOKOH ISLAM - Wifqi Atho'urrohman Nisak (PREMIERE : Journal of Islamic Elementary Education, 2022)
Learning is a very vital human activity compared to other creatures in this world. Learning is also a basic process of the development of human life. With the existence of learning activities, humans make qualitative changes to individuals so that their behavior will develop. In learning, there are also three domains, namely the cognitive domain, the affective domain and the psychomotor domain which are interconnected with gross motor skills such as throwing, winning, and kicking. Motor is also like writing and drawing. Islamic figures also color by offering their concepts. ranging from the concept of classical education to the concept of contemporary education. In terms of the concept of classical education, there are several figures who offer the concept of Islamic education such as Al-Gazali and al-Zarnuji. Al-Gazali was a great scholar who spent most of his time deepening scientific treasures from various aspects. In the discussion of this article or paper the author finds results regarding the concept of learning according to Islam which includes learning in the view of the Qur'an and Hadith, the importance of learning according to the Qur'an, ways of learning, learning facilities, and Islamic shops, namely Al -Ghazali and Al-Zarnuji.